“Bunny! O! Bunny!”: The Burney family in Oceania - Scobie, R (Duke University Press, 2018)
In the world of Frances Burney’s fiction, the South Seas do not seem to exist. Burney’s characters do not discuss the latest discoveries, read accounts of Pacific islands, dine with Oceanic natives, or admire, collect, or copy curiosities from Tahiti, New Zealand, or Hawaii. Yet members of Burney’s family, as inhabitants of a late eighteenth-century London saturated by the exotic, participated in all these activities. They had particular interest in, as well as privileged access to, Oceanic material, through Frances’s brother James, a naval officer who traveled on two expeditions with James Cook between 1772 and 1780. What the family called “Jemm’s Otaehitie Merchandize” included material objects, but also social connections, texts, and knowledge. This article outlines how these were used by James and Frances, their cousin Edward Francisco Burney, and Hester Thrale, to create real and imagined costumes for self-promotion, and to assert expertise, fashionability, and cosmopolitanism. Celebrations of James Burney’s adventures in Oceania, however, were disturbed by his recollections of violent scenes in New Zealand, which were so traumatic that he could only mention them in whispers, and so shocking that his sister left a space rather than write about them in her journal. I suggest, then, that public displays of Tahitian “Merchandize” always involved careful navigation between contradictory perceptions of Oceania as a setting for pleasure and horror, a source of enlightenment and of outrage.